2021
DOI: 10.3389/fpsyg.2020.599429
|View full text |Cite
|
Sign up to set email alerts
|

Interoception and Empathy Impact Perspective Taking

Abstract: Adopting the perspective of another person is an important aspect of social cognition and has been shown to depend on multisensory signals from one’s own body. Recent work suggests that interoceptive signals not only contribute to own-body perception and self-consciousness, but also to empathy. Here we investigated if social cognition – in particular adopting the perspective of another person – can be altered by a systematic manipulation of interoceptive cues and further, if this effect depends on empathic abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Thus, even though interoception is well known to underpin one's own emotional experience, its role in social cognition remains mainly correlational and largely unexplored. In fact, to date, only one study has examined whether interoception impacts perspective taking (Heydrich et al, 2021) yet, this study only focused on differences in spatial perspective taking.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even though interoception is well known to underpin one's own emotional experience, its role in social cognition remains mainly correlational and largely unexplored. In fact, to date, only one study has examined whether interoception impacts perspective taking (Heydrich et al, 2021) yet, this study only focused on differences in spatial perspective taking.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, in the shape-label matching paradigm with newly and temporarily associated self-relevant stimuli of the present study, the interoceptive information did not function effectively in associating external stimuli with the self, while interoception can enhance the self-relevant processing of external stimuli when the stimuli and tasks are different. For example, previous studies have reported that observation of fake bodily stimuli pulsating in synchrony with the participant’s heartbeat induced the experience of body-ownership over the fake bodily stimuli ( Aspell et al, 2013 ; Suzuki et al, 2013 ; Heydrich et al, 2018 , 2021 ). These results suggest that the processing of one’s own interoceptive information is a cue that brings about self-relevance to external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ambrosini et al (2019) reported that cardiac interoceptive information speeds up recognizing one’s own face. Moreover, observation of a fake body pulsating in synchrony with one’s heartbeat induces the feeling that a fake body is one’s own (i.e., a sense of body-ownership; Aspell et al, 2013 ; Suzuki et al, 2013 ; Heydrich et al, 2018 , 2021 ). These findings revealed that interoception contributes to self-relevant processing.…”
Section: Introductionmentioning
confidence: 99%
“…We recruited actors to address this question because of the centrality of accurate self-perception and awareness to their profession generally, and especially within the domain of physiology and emotion (Gosselin et al, 1995; Stanislavsky, 1952; Strasberg, 1987). Because of the established connection between interoception and emotional experience (Barrett et al, 2004; Critchley et al, 2004; Khalsa et al, 2018; Wiens et al, 2000), empathy (Ernst et al, 2013; Heydrich et al, 2021; Terasawa et al, 2014), and emotion regulation (Kever et al, 2015), we think it likely that the enhanced metacognitive awareness in actors identified here will facilitate actors’ emotion-related abilities, as the awareness of the perception of internal physiological signals would likely be relevant to the ability to effectively create, express, and convey emotion as an actor, though this is of course an empirical question. There is also the potential for these factors to be additionally related to other important emotion constructs like emotional awareness or intelligence (e.g., Ashkanasy & Dasborough, 2003; Lane et al, 1990; Salovey & Grewal, 2005), emotion expression (e.g., Elfenbein et al, 2002; Matsumoto et al, 2008), or affective synchrony (e.g., Wood et al, 2021) which could be examined by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interoceptive accuracy, defined as the extent to which one makes correct interoceptive judgments, contributes to individual differences in the role of emotion in a variety of domains. Better interoceptors report more intense emotional experiences (Barrett et al, 2004; Wiens et al, 2000), perhaps especially in the negative domain (Critchley et al, 2004), experience greater empathy for others (Ernst et al, 2013; Heydrich et al, 2021; Terasawa et al, 2014), and use emotion regulation more often (Kever et al, 2015). Similarly, interoceptive accuracy is relevant to issues of mental health (Khalsa et al, 2018), including alcohol (Ateş Çöl et al, 2016) and drug dependence (Gray & Critchley, 2007; Stewart, Juavinett, et al, 2015; Stewart, May, et al, 2015) and may contribute to autism spectrum disorder (Garfinkel et al, 2016) and other psychiatric disorders (Bonaz et al, 2021).…”
mentioning
confidence: 99%